Manajemen Ekstrakurikuler Iqra’ Bil Qalam dalam Penguatan Literasi Al-Qur'an dan Karakter Religius Peserta Didik - Shofiyatul Hilmah; Erma Fatmawati; Lailatul Usriyah (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2026)
The management of Qur'anic literacy programs plays a strategic role in strengthening students' religious character in Islamic schools. However, previous studies have predominantly examined the effectiveness of the Iqra’ Bil Qalam method from an instructional perspective, while its management process has received limited attention. This study aims to analyze the management of the Iqra’ Bil Qalam extracurricular program in strengthening Qur'anic literacy at Madrasah Aliyah Ashri Jember using Terry & Rue’s management functions (Planning, Organizing, Actuating, and Controlling). A qualitative descriptive approach was employed. Data were collected through observations, semi-structured interviews, and document analysis involving the principal, vice principal, extracurricular coordinator, homeroom teacher, and students selected through purposive sampling until data saturation was achieved. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña through open coding, categorization, theme development, and cross-data verification. The findings indicate that the program is managed through four integrated management functions. Planning is based on institutional vision and program evaluation, organizing is implemented through clear task distribution and coordination, actuating emphasizes the follow the line method accompanied by teacher facilitation, while controlling is conducted through monitoring, tashih, periodic evaluation, and verification of students' achievement. The study also identifies several implementation challenges, including limited program innovation, students' learning fatigue, and the absence of a structured reward system. This study proposes a Conceptual Model of Iqra’ Bil Qalam Extracurricular Management, demonstrating that effective management supported by school leadership, teacher commitment, school culture, and student participation strengthens Qur'anic literacy, fosters students' religious character, and promotes a sustainable Qur'anic literacy culture within the madrasah.